Dual lysine and N-terminal acetyltransferases reveal the complexity underpinning protein acetylation - Willy V Bienvenut; Annika Brünje; Jean‐Baptiste Boyer; Jens S Mühlenbeck; Gautier Bernal; Ines Lassowskat; Cyril Dian; Eric Linster; Trinh V Dinh; Minna M Koskela; Vincent Jung; Julian Seidel; et al. (WILEY, 2022)
Protein acetylation is a highly frequent protein modification. However, comparatively little is known about its enzymatic machinery. N-alpha-acetylation (NTA) and epsilon-lysine acetylation (KA) are known to be catalyzed by distinct families of enzymes (NATs andKATs, respectively), although the possibility that the sameGCN5-relatedN-acetyltransferase (GNAT) can perform both functions has been debated. Here, we discovered a new family of plastid-localizedGNATs, which possess a dual specificity. All characterizedGNATfamily members display a number of unique features. Quantitative mass spectrometry analyses revealed that these enzymes exhibit both distinctKAand relaxedNTAspecificities. Furthermore, inactivation ofGNAT2 leads to significantNTAorKAdecreases of several plastid proteins, while proteins of other compartments were unaffected. The data indicate that these enzymes have specific protein targets and likely display partly redundant selectivity, increasing the robustness of the acetylation processin vivo. In summary, this study revealed a new layer of complexity in the machinery controlling this prevalent modification and suggests that other eukaryoticGNATs may also possess these previously underappreciated broader enzymatic activities.